1996
DOI: 10.1111/1523-1747.ep12328204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Nitric Oxide Synthase in Human Skin

Abstract: The aim of this study was to investigate in human skin in vivo the role of nitric oxide in maintaining resting vascular tone, in the vasodilatation caused by local warming and by ultraviolet B light exposure, and in the response to exogenous calcitonin gene-related peptide (CGRP). Cutaneous blood flow was assessed by planimetry of the visible erythema or pallor and by laser Doppler flowmetry. Intradermal injection of the inhibitor of nitric oxide synthase, NG-nitro-L-arginine methyl ester (L-NAME; 25 nmol), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 38 publications
5
59
0
1
Order By: Relevance
“…This would suggest that in rabbit skin the vasodilator mechanism of CGRP is independent of NO, whereas NO may play an important role in the release of CGRP from capsaicin-sensitive nerves. In contrast, Goldsmith et al (1996) were able to inhibit CGRP-induced DBF increase by injecting L-NMMA into skin of the human forearm. Our findings indicate that, in the human skin, NO is neither involved in the release of CGRP nor in its vasodilator mechanism.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 253mentioning
confidence: 76%
“…This would suggest that in rabbit skin the vasodilator mechanism of CGRP is independent of NO, whereas NO may play an important role in the release of CGRP from capsaicin-sensitive nerves. In contrast, Goldsmith et al (1996) were able to inhibit CGRP-induced DBF increase by injecting L-NMMA into skin of the human forearm. Our findings indicate that, in the human skin, NO is neither involved in the release of CGRP nor in its vasodilator mechanism.…”
Section: Mediators Of Capsaicin-induced Dermal Vasodilation 253mentioning
confidence: 76%
“…Attenuation of electrically and mustard oil-induced neurogenic protein extravasation and vasodilation has been reported in some rodent studies [9, 10, 11, 12], whereas no significant role was found in others [13, 14]. Similarly, experiments in humans studying the role of NO on neuropeptide-induced vascular responses provide controversial results [15, 16, 17, 18]. The unequivocal results might reflect the complex interaction of NO and neuropeptides: there is evidence for neuropeptide-induced NO release, especially in the splanchnic vasculature [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is, however, masked in global blood flow measures, and the result is that total blood flow is seen to be reduced to a similar extent as the oxygen extraction is increased (and thus no changes in V O 2 are detected). Interestingly, in this respect, especially skin blood flow is pronouncedly decreased during NOS inhibition (7,11), but also resting blood flow in subcutaneous adipose tissue is largely dependent on NO (1). However, blood flow decreases in adipose tissue may not be the most important explanatory factor, since it was found in the current study that NOS inhibition at rest decreased adipose tissue blood flow to a similar degree as in muscle (Fig.…”
Section: Discussionmentioning
confidence: 99%